Application of data pooling to longitudinal studies of early post-traumatic stress disorder (PTSD): the International Consortium to Predict PTSD (ICPP) project - Qi, Wei; Ratanatharathorn, Andrew; Gevonden, Martin; Bryant, Richard; Delahanty, Douglas; Matsuoka, Yutaka; Olff, Miranda; deRoon-Cassini, Terri; Schnyder, Ulrich; Seedat, Soraya; Laska, Eugene; Kessler, Ronald C.; et al. (European journal of psychotraumatology, 2018)
Background: Understanding the development of post-traumatic stress disorder (PTSD) is a precondition for efficient risk assessment and prevention planning. Studies to date have been site and sample specific. Towards developing generalizable models of PTSD development and prediction, the International Consortium to Predict PTSD (ICPP) compiled data from 13 longitudinal, acute-care based PTSD studies performed in six different countries. Objective: The objectives of this study were to describe the ICPP's approach to data pooling and harmonization, and present cross-study descriptive results informing the longitudinal course of PTSD after acute trauma. Methods: Item-level data from 13 longitudinal studies of adult civilian trauma survivors were collected. Constructs (e.g. PTSD, depression), measures (questions or scales), and time variables (days from trauma) were identified and harmonized, and those with inconsistent coding (e.g. education, lifetime trauma exposure) were recoded. Administered in 11 studies, the Clinician Administered PTSD Scale (CAPS) emerged as the main measure of PTSD diagnosis and severity. Results: The pooled data set included 6254 subjects (39.9% female). Studies' average retention rate was 87.0% (range 49.1-93.5%). Participants' baseline assessments took place within 2 months of trauma exposure. Follow-up durations ranged from 188 to 1110 days. Reflecting studies' inclusion criteria, the prevalence of baseline PTSD differed significantly between studies (range 3.1-61.6%), and similar differences were observed in subsequent assessments (4.3-38.2% and 3.8-27.0% for second and third assessments, respectively). Conclusion: Pooling data from independently collected studies requires careful curation of individual data sets for extracting and optimizing informative commonalities. However, it is an important step towards developing robust and generalizable prediction models for PTSD and can exceed findings of single studies. The large differences in prevalence of PTSD longitudinally cautions against using any individual study to infer trauma outcome. The multiplicity of instruments used in individual studies emphasizes the need for common data elements in future studies.